Neonatal Transportation Device with Antimicrobial Properties (Research, Society and Development, 2022)
The transport of newborns implies the guarantee of a safe, comfortable and contamination-free handling, in view of the greater risk of contact of the baby with pathological agents in the hospital environment. Considering the antimicrobial capacity of chitosan and the possibility of depositing it on tissues, this work aimed to develop a neonatal transport system for newborns at normal risk (Baby-Bag) impregnated with this polymer. Starting from the briefing, hand drawings and image manipulation software were developed to better express the suggested concepts, followed by the 3D rendering of Baby-Bag. The samples were produced in Ribana type mesh (200g/m²). For chitosan impregnation, the blasting method was used, with polymer solutions at different concentrations (0.5; 1 and 2 %), followed by neutralization. Then, the meshes were characterized by Optical Microscopy (OM), Fourier Transform Infrared Spectroscopy (FTIR), Tensile Strength, Antimicrobial Activity and Citotoxicity. The MO and FTIR techniques indicated a partial detachment/loss of the chitosan impregnation during the washing and drying processes, while the mechanical test indicated that the chitosan incorporation increased the elastic modulus of the fabrics. According to the biological results, it can be stated that the material is non-toxic and has gram-positive (Staphylococcus aureus) and gram-negative (Escherichia coli) antimicrobial activity. Thus, it can be concluded that the neonatal transport system for newborns has the potential to be used as safe maternal and child transport.